2016
DOI: 10.3390/ijms17071122
|View full text |Cite
|
Sign up to set email alerts
|

Niemann-Pick Type C2 Protein Mediates Hepatic Stellate Cells Activation by Regulating Free Cholesterol Accumulation

Abstract: In chronic liver diseases, regardless of their etiology, the development of fibrosis is the first step toward the progression to cirrhosis, portal hypertension, and hepatocellular carcinoma. Hepatic stellate cells (HSCs) are the main profibrogenic cells that promote the pathogenesis of liver fibrosis, and so it is important to identify the molecules that regulate HSCs activation and liver fibrosis. Niemann-Pick type C2 (NPC2) protein plays an important role in the regulation of intracellular cholesterol homeos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…7,8 Another group reported that regulation of FC accumulation by the Niemann-Pick type C2 protein plays a key role in TGFβ-induced HSC activation. 9 We further showed that HSC activation downregulated peroxisome proliferator-activated receptor-γ (PPARγ) signaling, which led to enhanced signaling by sterol regulatory element-binding protein 2 (SREBP2) and microRNA-33a (miR-33a); this resulted in increased FC accumulation through upregulation of low-density lipoprotein receptor (LDLR) expression and diminished expression of ATP-binding cassette transporter A1 (ABCA1). 10 These findings suggest that FC accumulation in HSCs contributes to a "vicious cycle" of HSC activation, which occurs even under non-high-cholesterol conditions, and could function as a mediator in promoting HSC activation.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…7,8 Another group reported that regulation of FC accumulation by the Niemann-Pick type C2 protein plays a key role in TGFβ-induced HSC activation. 9 We further showed that HSC activation downregulated peroxisome proliferator-activated receptor-γ (PPARγ) signaling, which led to enhanced signaling by sterol regulatory element-binding protein 2 (SREBP2) and microRNA-33a (miR-33a); this resulted in increased FC accumulation through upregulation of low-density lipoprotein receptor (LDLR) expression and diminished expression of ATP-binding cassette transporter A1 (ABCA1). 10 These findings suggest that FC accumulation in HSCs contributes to a "vicious cycle" of HSC activation, which occurs even under non-high-cholesterol conditions, and could function as a mediator in promoting HSC activation.…”
Section: Introductionmentioning
confidence: 97%
“…Recently, we showed that the accumulation of free cholesterol (FC) in HSCs sensitized the cells to activation by transforming growth factor‐β (TGFβ) by augmenting Toll‐like receptor 4 (TLR4) signaling and the subsequent inhibition of the expression of TGFβ‐pseudoreceptor Bambi (bone morphogenetic protein and activin membrane‐bound inhibitor) . Another group reported that regulation of FC accumulation by the Niemann‐Pick type C2 protein plays a key role in TGFβ‐induced HSC activation . We further showed that HSC activation downregulated peroxisome proliferator‐activated receptor‐γ (PPARγ) signaling, which led to enhanced signaling by sterol regulatory element‐binding protein 2 (SREBP2) and microRNA‐33a (miR‐33a); this resulted in increased FC accumulation through upregulation of low‐density lipoprotein receptor (LDLR) expression and diminished expression of ATP‐binding cassette transporter A1 (ABCA1) .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Twu et al[ 38 ] demonstrated that NPC2 overexpression attenuates TGF-β sensitization by mobilizing cholesterol. The authors concluded that NPC2 might prove an effective agent against liver fibrosis progression.…”
Section: Discussionmentioning
confidence: 99%
“…LX2 cells and HSC-T6 cells (an immortalized strain of rat HSCs) (Twu et al, 2016) were cultured in Dulbecco's modified Eagle's medium (DMEM; Gibco BRL, Grand Island, NY, USA) with 1% heat-inactivated fetal bovine serum (FBS; HyClone, Logan, UT, USA), penicillin and streptomycin (100 U/ml), nonessential amino acids (0.1 mM), and L-glutamine (2 mM) at 37°C in a 5% CO 2 incubator. Murine RAW264.7 macrophages (Bioresource Collection and Research Center, BCRC 60001, Taiwan) were cultured in DMEM supplemented with 10% FBS, penicillin and SCHEME 1 | Synthesis of compound 4a, 4b, 4c, and 5.…”
Section: Cell Culturementioning
confidence: 99%